Development Of Indonesian-Arabic Language Translation Teaching Strategies With Cultural Understanding/ تطوير استراتيجيات تعليم ترجمة اللغة الإندونيسية للعربية في ضوء المفهوم الثقافي - Mubarak, Faisal; Rahman, Ahmad Abdul; Althobaiti, Naif Abdul Aziz; Deviana, Ade Destri (Ijaz Arabi Journal of Arabic Learning, 2025)
This study aims to develop teaching strategies for translating Indonesian-Arabic from a cultural perspective that includes translating strategy documents, methods, procedures, and translating rules and factors that encourage students majoring in Choosing Translating strategies. This research methodology is descriptive qualitative research; data were sourced from 45 students who were randomly selected at three universities in the Department of Arabic Language Education in Indonesia, namely Antasari State Islamic University Banjarmasin, University of Qur’an Amuntai, and University of Darul Hijrah Martapura. Interviews and documentation search techniques were used to collect the data. The result of this study is the teaching of translating Indonesia to Arabic led to literal translation according to grammatical and morphological rules, without attention to cultural understanding, because many Arabic languages no equivalent in Indonesia, and understand the culture of both Indonesian and Arabic, and are influenced by ways of thinking in the Indonesian language system, so that most students follow the way of thinking in Indonesian when translating.